(untitled) (Journal of Humanitarian and Applied Sciences, 2020)
S(X) is the semigroup, under composition, of all continuous selfmaps of the topological space X. In this paper, we show for a number of spaces that S(X) contains a dense subsemigroup generated by two elements when S(X) given the compact-open topology.